Consumer Healthy Eating 2019 dataset - Ho, Peter; Ledger, Georgina (University of Leeds, 2021)
This dataset contains data on perceived compliance to the UK Eatwell guide (15 items) and food consumption (11 items) from a survey in 2019 of UK consumers (n=301) . Demographic data (Type of Diet, Ethnicity, Gender and Age) and exercise duration were also collected.
Keywords: FOS: Health sciences